A method for preparing fully orthorhombic single-crystal iron phosphate

Through the preparation method of fully orthogonal crystalline iron phosphate, the problem of poor performance of lithium iron phosphate in the prior art is solved, and a high compaction density and excellent electrical performance of lithium iron phosphate products are realized, and the process is simple and energy consumption is low.

CN118814272BActive Publication Date: 2025-04-04XINYANGFENG AGRI TECH CO LTD +1

Patent Information

Application Number
CN202411052041.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2025-04-04
Estimated Expiration
2044-08-01

AI Technical Summary

Technical Problem

The iron phosphate produced by the existing iron phosphate preparation method is monoclinic crystalline and is a polycrystalline agglomerate, resulting in low compaction density of lithium iron phosphate and poor capacity, magnification and cycling performance.

Method used

The preparation method of fully orthogonal crystalline iron phosphate is adopted. By controlling the amount and pH of the oxidant, the crystallization and whitening reaction is carried out at a lower temperature to ensure that all ferrous ions are oxidized to form a single crystal particle iron phosphate with fully orthogonal crystalline form.

Benefits of technology

It improves the compaction density and electrical performance of lithium iron phosphate, enhances capacity, magnification and cycling performance, and has a simple process and low energy consumption, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118814272B_ABST
    Figure CN118814272B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of iron phosphate preparation, and specifically to a method for preparing a fully orthorhombic single crystal iron phosphate, comprising the following steps: S1, adding an oxidant to a reaction vessel containing a ferrous solution, controlling the amount of the oxidant so that after the addition of the oxidant, the mass percentage of the ferrous salt content in the reaction solution to the total solution is 1% to 5%; S2, adding a sodium phosphate solution to the reaction vessel; S3, adding phosphoric acid to the reaction vessel, adjusting the pH value of the reaction solution to 1.57 to 2.14, reacting at 50 to 60°C, adding an oxidant after the reaction material turns white until no ferrous ions are detected in the reaction solution, and filtering, washing, and drying the reaction product to obtain. The present invention has a simple process, a short process flow, a low reaction process temperature, and the reaction product does not require high-temperature calcination. It has the advantages of low energy consumption in the production process and high production efficiency, and can be mass-produced using an existing iron phosphate production line.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of iron phosphate preparation technology, and specifically to a method for preparing fully orthorhombic single-crystal iron phosphate. Background Technology

[0002] Lithium iron phosphate (LFP) batteries offer better safety performance, are more environmentally friendly, and offer better cost-effectiveness compared to ternary lithium batteries. Therefore, LFP batteries have a larger market share in power batteries and also dominate the energy storage battery market.

[0003] The mainstream method for preparing lithium iron phosphate (LFP) uses iron phosphate, lithium carbonate, and glucose as raw materials, which are then wet-milled and processed through drying, sintering, and crushing. Therefore, iron phosphate, as one of the raw materials, plays a crucial role in the preparation of LFP. It is generally believed that the compaction and electrical properties of LFP are mainly determined by iron phosphate. There are three common methods for preparing iron phosphate: the ammonium method, the sodium method, and the iron method. The ammonium method mainly uses ferrous sulfate (a byproduct of titanium dioxide) as the iron source and industrial monoammonium phosphate as the phosphorus source; the sodium method mainly uses ferrous sulfate (a byproduct of titanium dioxide) as the iron source and phosphoric acid as the phosphorus source, and uses sodium hydroxide to adjust the pH; the iron method mainly uses iron powder as the iron source and phosphoric acid as the phosphorus source. The dihydrate iron phosphate prepared by these three mainstream methods is all monoclinic iron phosphate. Monoclinic iron phosphate has low crystal structure symmetry and relatively low crystal structure stability; morphologically, the iron phosphate prepared by these three mainstream methods is a polycrystalline aggregate. Therefore, the lithium iron phosphate prepared using this method has a low compaction density, and the electrode material prepared has poor capacity, rate capability, and cycle performance. Summary of the Invention

[0004] To address the technical problem that the iron phosphate prepared by the above three mainstream methods is monoclinic and consists of polycrystalline aggregates, this invention provides a method for preparing fully orthorhombic single-crystal iron phosphate.

[0005] The technical solution of this invention is as follows:

[0006] A method for preparing fully orthorhombic single-crystal iron phosphate includes the following steps:

[0007] S1. Add oxidant to the reaction vessel containing ferrous solution, controlling the amount of oxidant so that after the oxidant is added, the ferrous salt content in the reaction solution accounts for 1% to 5% of the total mass of the solution;

[0008] S2. Add a sodium phosphate salt solution to the reaction vessel;

[0009] S3. Add phosphoric acid to the reaction vessel to adjust the pH of the reaction solution to 1.57~2.14. React at 50~60℃. After the reaction material turns white, add oxidant until no ferrous ions can be detected in the reaction solution, that is, all ferrous ions are oxidized. The reaction product is filtered, washed and dried to obtain fully orthorhombic single crystal iron phosphate.

[0010] Furthermore, the molar ratio of ferrous salt, oxidant, and sodium-containing phosphate salt is 1:0.6~0.8:1.1~1.2, where the oxidant is the sum of the oxidants used in steps S1 and S3.

[0011] Furthermore, in S1, the concentration of the ferrous solution is 0.4~0.9 mol / L;

[0012] In S2, the concentration of sodium phosphate salt is 0.4~0.9 mol / L.

[0013] Furthermore, in S1, the iron source of the ferrous solution is selected from at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, and ferrous oxalate, wherein the ferrous sulfate can be a pure substance or provided by titanium dioxide byproducts containing ferrous sulfate.

[0014] Furthermore, in S1, the oxidant is selected from at least one of hydrogen peroxide, air, oxygen, ozone, and sodium peroxide.

[0015] Furthermore, in S1, the oxidant is added while stirring at a speed of 150-550 rpm, preferably 300 rpm, and the oxidant is added over a period of 5-10 hours, preferably 8 hours.

[0016] Furthermore, in S1, the ferrous content in the reaction solution was determined by potassium permanganate titration.

[0017] Furthermore, in S2, the sodium phosphate solution is selected from at least one of trisodium phosphate solution, disodium phosphate solution, and monosodium phosphate solution.

[0018] Furthermore, in step S2, a sodium phosphate salt solution is added while stirring at a speed of 150-550 rpm, preferably 300 rpm, and the sodium phosphate salt solution is added over a period of 15-20 hours, preferably 18 hours.

[0019] Furthermore, in S3, no ferrous ions were detected in the reaction solution, meaning that all ferrous ions were oxidized to ferric ions, and the solution was kept at this temperature for 10-15 hours.

[0020] Furthermore, in S3, the reaction product is filtered, washed until the conductivity of the wash water is <3000 μs / cm, and then dried at 120℃ for 2~5 h.

[0021] Furthermore, in S3, the ferrous content in the reaction solution was determined by potassium ferricyanide titration.

[0022] The beneficial effects of this invention are as follows:

[0023] This invention uses a low-concentration ferrous solution and a sodium phosphate solution. First, the ferrous salt is oxidized to an iron salt solution. The amount of oxidant added is controlled to retain 1% to 5% ferrous salt in the solution. Then, the sodium phosphate is slowly added dropwise to the iron salt solution to control the nucleation and growth process of ferric phosphate. A crystallization and whitening reaction is carried out at a low temperature. After whitening, an oxidant is added to oxidize all 1% to 5% ferrous salt to ferric iron. After that, the solution is kept at a relatively long temperature to finally obtain a fully orthorhombic single-crystal ferric phosphate product.

[0024] The method for preparing fully orthogonal single-crystal iron phosphate provided by this invention is simple, has a short process flow, low reaction temperature, and does not require high-temperature calcination of the reaction products. It has the advantages of low energy consumption and high production efficiency, and can be scaled up using existing iron phosphate production lines.

[0025] Unlike conventional methods that produce small, plate-like monoclinic crystals of iron phosphate, this invention produces single-crystal, fully orthorhombic crystals of iron phosphate. Lithium iron phosphate products prepared using single-crystal, fully orthorhombic iron phosphate exhibit high compaction density, high capacity, and excellent rate capability and cycle performance. The production process of this invention is simple and has a short flow rate. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 These are the XRD patterns of ferric phosphate prepared in Example 3 and the standard card of orthorhombic ferric phosphate.

[0028] Figure 2 This is a SEM image (1000x magnification) of the iron phosphate prepared in Example 3.

[0029] Figure 3 This is a SEM image (10,000x magnification) of the iron phosphate prepared in Example 3.

[0030] Figure 4 The images show the XRD pattern of ferric phosphate prepared in Example 5 and the standard card of orthorhombic ferric phosphate.

[0031] Figure 5 This is a SEM image (1000x magnification) of the iron phosphate prepared in Example 5.

[0032] Figure 6This is a SEM image (magnified 10,000 times) of the iron phosphate prepared in Example 5.

[0033] Figure 7 The images show the XRD pattern of iron phosphate prepared in Comparative Example 1 and the standard card for monoclinic iron phosphate.

[0034] Figure 8 This is a SEM image (magnified 1000 times) of the secondary agglomerates of iron phosphate prepared in Comparative Example 1.

[0035] Figure 9 This is a SEM image (magnified 10,000 times) of the primary iron phosphate particles prepared in Comparative Example 1.

[0036] Figure 10 The images show the XRD pattern of iron phosphate prepared in Comparative Example 2 and the standard card of monoclinic iron phosphate.

[0037] Figure 11 This is a SEM image (1000x magnification) of the secondary aggregates of ferric phosphate prepared in Comparative Example 2.

[0038] Figure 12 This is a primary particle SEM image (magnified 10,000 times) of the iron phosphate prepared in Comparative Example 2.

[0039] Figure 13 The images show the XRD pattern of iron phosphate prepared in Comparative Example 3 and the standard card for monoclinic iron phosphate.

[0040] Figure 14 This is a SEM image (1000x magnification) of the secondary aggregates of ferric phosphate prepared in Comparative Example 3.

[0041] Figure 15 This is a primary particle SEM image (magnified 10,000 times) of the iron phosphate prepared in Comparative Example 3.

[0042] Figure 16 This is a comparison chart of the rate performance of the #3 and #6 clasp batteries in Application Example 1.

[0043] Figure 17 This is a comparison chart of the cycle performance of the #3 and #6 clasp in Application Example 1. Detailed Implementation

[0044] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention. Where specific conditions are not specified in the embodiments of this invention, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0045] Example 1

[0046] A method for preparing fully orthorhombic single-crystal iron phosphate includes the following steps:

[0047] (1) Prepare 5L of 0.8mol / L ferrous sulfate solution, 5L of 0.7mol / L hydrogen peroxide solution and 4.9L of 0.9mol / L trisodium phosphate solution respectively;

[0048] (2) Add 5L of ferrous sulfate solution to the reaction vessel. The stirring speed of the reaction vessel is 300rpm. Add hydrogen peroxide to the reaction vessel at room temperature for 8 hours. Control the amount of hydrogen peroxide added. Detect the ferrous ions in the reaction solution by potassium permanganate titration. Make sure there is still 3% ferrous sulfate in the reaction vessel.

[0049] (3) Slowly add 4.9L of trisodium phosphate solution to the reactor over a period of 18 hours, and stir the reactor at 300rpm.

[0050] (4) Add phosphoric acid to the reaction vessel and adjust the pH of the reaction solution to 1.59. React at 55°C. When the reaction material turns white, add hydrogen peroxide until no ferrous ions can be detected in the reaction solution, that is, the remaining 3% ferrous sulfate is completely oxidized to ferric sulfate (the color does not change when tested with potassium ferricyanide). At this time, 1.57L of 0.7mol / L hydrogen peroxide remains. Then keep warm for 12h. The reaction product is filtered and washed until the conductivity of the wash water is <3000μs / cm. Dry at 120°C for 3h to obtain ferric phosphate.

[0051] The obtained iron phosphate product was subjected to XRD and SEM tests. The results showed that the iron phosphate product prepared in Example 1 was a fully orthorhombic single crystal iron phosphate.

[0052] Example 2

[0053] A method for preparing fully orthorhombic single-crystal iron phosphate includes the following steps:

[0054] (1) Prepare 10L of 0.8mol / L ferrous chloride solution, 10L of 0.9mol / L hydrogen peroxide solution and 10L of 0.9mol / L disodium phosphate solution respectively;

[0055] (2) Add 10L of ferrous chloride solution to the reactor. The stirring speed of the reactor is 300rpm. Add hydrogen peroxide to the reactor at room temperature for 9h. Control the amount of hydrogen peroxide added. Detect the ferrous ions in the reaction solution by potassium permanganate titration. Make sure there is still 3% ferrous chloride in the reactor.

[0056] (3) Slowly add 10L of disodium phosphate solution to the reactor over a period of 19 hours, and stir the reactor at 300 rpm.

[0057] (4) Add phosphoric acid to the reaction vessel and adjust the pH of the reaction solution to 1.67. React at 55°C. When the reaction material turns white, add hydrogen peroxide until no ferrous ions can be detected in the reaction solution, that is, the remaining 3% ferrous chloride is completely oxidized to ferric chloride (the color does not change when tested with potassium ferricyanide). At this time, 4.22L of 0.9mol / L hydrogen peroxide remains. Then keep warm for 13h. The reaction product is filtered and washed until the conductivity of the wash water is <3000μs / cm. Dry at 120°C for 3h to obtain ferric phosphate.

[0058] The obtained iron phosphate product was subjected to XRD and SEM tests. The results showed that the iron phosphate product prepared in Example 2 was a fully orthorhombic single crystal iron phosphate.

[0059] Example 3

[0060] A method for preparing fully orthorhombic single-crystal iron phosphate includes the following steps:

[0061] (1) Prepare 100L of 0.8mol / L ferrous sulfate solution, 105L of 0.8mol / L hydrogen peroxide solution and 137L of 0.7mol / L trisodium phosphate solution respectively;

[0062] (2) Add 100L of ferrous sulfate solution to the reactor. The stirring speed of the reactor is 300rpm. Add hydrogen peroxide to the reactor at room temperature for 8 hours. Control the amount of hydrogen peroxide added. Detect the ferrous ions in the reaction solution by potassium permanganate titration. Make sure there is still 3% ferrous sulfate in the reactor.

[0063] (3) Slowly add 137L of trisodium phosphate solution to the reactor over a period of 19 hours, and stir the reactor at 300 rpm.

[0064] (4) Add phosphoric acid to the reaction vessel and adjust the pH of the reaction solution to 1.59. React at 60°C. When the reaction material turns white, add hydrogen peroxide until no ferrous ions can be detected in the reaction solution, that is, the remaining 3% ferrous sulfate is completely oxidized to ferric sulfate (the color does not change when tested with potassium ferricyanide). At this time, 25L of 0.8mol / L hydrogen peroxide remains. Then keep warm for 14h. The reaction product is filtered and washed until the conductivity of the wash water is <3000μs / cm. Dry at 120°C for 3h to obtain ferric phosphate.

[0065] The obtained ferric phosphate product was tested by XRD and SEM, and the results are as follows: Figure 1-3 As shown. By Figure 1 It can be seen that the iron phosphate crystals prepared in Example 3 are pure-phase, orthorhombic crystals. Figure 2-3 It can be seen that the iron phosphate crystals prepared in Example 3 are single-crystal dispersed particles. This indicates that the iron phosphate product prepared in Example 3 is a fully orthorhombic single-crystal iron phosphate.

[0066] In this example 3, a low concentration of ferrous salt (0.8 mol / L) and sodium phosphate salt (0.7 mol / L) were used. The sodium phosphate salt was added slowly (0.63 L / min) and for a long time (19 h). As a result, there were fewer nuclei of ferric phosphate and the growth rate was slow. Furthermore, at a relatively high pH value (pH=1.59), the supersaturation of the crystal nucleus surface was reduced due to the adsorption and interference of ferrous ions on the crystal nucleus surface during crystallization, which was conducive to the formation of orthorhombic single crystal particles.

[0067] Example 4

[0068] A method for preparing fully orthorhombic single-crystal iron phosphate includes the following steps:

[0069] (1) Prepare 100 L of 0.4 mol / L ferrous nitrate solution and 120 L of 0.4 mol / L sodium monophosphate solution respectively;

[0070] (2) Add 100L of ferrous nitrate solution to the reaction vessel. The stirring speed of the reaction vessel is 150rpm. At room temperature, oxygen is introduced into the reaction vessel. The oxygen introduction time is controlled. The ferrous ions in the reaction solution are detected by potassium permanganate titration. The reaction vessel solution still contains 5% ferrous nitrate by mass.

[0071] (3) Slowly add 120L of sodium monophosphate solution to the reactor over a period of 15 hours, and stir the reactor at 150 rpm.

[0072] (4) Add phosphoric acid to the reactor and adjust the pH of the reaction solution to 2.14. React at 60°C. After the reaction material turns white, oxygen is introduced until no ferrous ions can be detected in the reaction solution, that is, the remaining 5% ferrous nitrate is completely oxidized to ferric nitrate (the color does not change when tested with potassium ferricyanide). Then keep warm for 10 hours. The reaction product is filtered and washed until the conductivity of the wash water is <3000μs / cm. Dry at 120°C for 5 hours to obtain ferric phosphate.

[0073] In other embodiments of the invention, air or ozone may be introduced instead of oxygen.

[0074] Example 5

[0075] A method for preparing fully orthorhombic single-crystal iron phosphate includes the following steps:

[0076] (1) Prepare 100L of 0.6mol / L ferrous oxalate solution, 100L of 0.5mol / L sodium peroxide solution and 115L of 0.6mol / L monosodium phosphate solution respectively;

[0077] (2) Add 100L of ferrous oxalate solution to the reaction vessel. The stirring speed of the reaction vessel is 550rpm. Add sodium peroxide solution to the reaction vessel at room temperature for 5h. Control the amount of sodium peroxide added. Detect the ferrous ions in the reaction solution by potassium permanganate titration. Make sure there is still 1% ferrous oxalate in the reaction vessel.

[0078] (3) Slowly add 115L of sodium monophosphate solution to the reactor over a period of 20 hours, and stir the reactor at 550 rpm.

[0079] (4) Add phosphoric acid to the reaction vessel and adjust the pH of the reaction solution to 2.04. React at 60°C. When the reaction material turns white, add sodium peroxide solution until no ferrous ions can be detected in the reaction solution, that is, the remaining 1% ferrous oxalate is completely oxidized to ferric oxalate (the color does not change when tested with potassium ferricyanide). At this time, there is still 4L of 0.5mol / L sodium peroxide solution remaining. Then keep warm for 15h. The reaction product is filtered and washed until the conductivity of the wash water is <3000μs / cm. Dry at 120°C for 2h to obtain ferric phosphate.

[0080] The obtained ferric phosphate product was tested by XRD and SEM, and the results are as follows: Figure 4-6 As shown. By Figure 4 It can be seen that the iron phosphate crystals prepared in Example 5 are, like those in Example 3, a pure-phase, orthorhombic crystal form. Figure 5-6 It can be seen that the iron phosphate crystals prepared in Example 5 are the same as those in Example 3, and are in the form of single-crystal dispersed particles.

[0081] Comparative Example 1

[0082] A method for preparing fully orthorhombic single-crystal iron phosphate includes the following steps:

[0083] (1) Prepare 100L of 1.7mol / L ferrous sulfate solution, 114L of 1.2mol / L hydrogen peroxide solution and 110L of 1.8mol / L trisodium phosphate solution respectively;

[0084] (2) Add 100L of ferrous sulfate solution to the reactor. The stirring speed of the reactor is 300rpm. Add hydrogen peroxide to the reactor at room temperature for 60min.

[0085] (3) Use potassium ferricyanide to test whether there is ferrous iron in the reaction solution. If there is ferrous iron, add hydrogen peroxide until there is no ferrous iron. After the potassium ferricyanide test does not change color, add 110L of trisodium phosphate solution to the reaction vessel. The addition time is 60min. The stirring speed of the reaction vessel is 300rpm.

[0086] (4) Add phosphoric acid to the reaction vessel, adjust the pH of the reaction solution to 1.0, react at 80℃ for 2h, filter and wash the reaction product until the conductivity of the wash water is <3000μs / cm, and dry at 120℃ for 3h to obtain iron phosphate.

[0087] The obtained ferric phosphate product was tested by XRD and SEM, and the results are as follows: Figure 7-9 As shown. By Figure 7 It can be seen that the iron phosphate crystals prepared in Comparative Example 1 are of the conventional monoclinic crystal form. From Figure 8 It can be seen that the secondary aggregates of iron phosphate crystals prepared in Comparative Example 1 are conventional micron-sized polycrystalline spherical structures (5-10 μm). From Figure 9 It can be seen that the primary particles of the iron phosphate product prepared in Comparative Example 1 are small flakes of nanoscale size (50-100nm).

[0088] The reason for the difference in crystal structure between the iron phosphate products in Comparative Example 1 is that Comparative Example 1 used high concentrations of ferrous salt (1.7 mol / L) and sodium phosphate (1.8 mol / L), and the sodium phosphate was added quickly (1.83 L / min) and for a short time (60 min). As a result, iron phosphate nucleated quickly and produced more nuclei, and its growth rate was also fast. Furthermore, at a lower pH value (pH=1.0), the formation of orthorhombic single crystal particles was inhibited.

[0089] The crystal forms and cell parameters of iron phosphate and lithium iron phosphate in Example 3 and Comparative Example 1 were further compared. Table 1 shows that Comparative Example 1 prepared a monoclinic iron phosphate, while Example 3 prepared a fully orthorhombic iron phosphate. When using these two different crystal forms of iron phosphate to prepare lithium iron phosphate, the monoclinic crystal form has lower symmetry than the fully orthorhombic crystal form, and because of the different crystal forms, it is more difficult to transform monoclinic iron phosphate into fully orthorhombic lithium iron phosphate compared to transforming fully orthorhombic iron phosphate into fully orthorhombic lithium iron phosphate. Furthermore, the lattice parameters b and c of orthorhombic iron phosphate are close to those of monoclinic iron phosphate, but the a value of orthorhombic iron phosphate (a=10.122) is closer to that of orthorhombic lithium iron phosphate (a=10.390). Therefore, from a thermodynamic perspective, orthorhombic iron phosphate may have a lower Gibbs free energy when transforming into lithium iron phosphate compared to monoclinic iron phosphate (a=5.329), making it easier to transform into orthorhombic lithium iron phosphate. Thirdly, from a kinetic perspective, the unit cell volume of orthorhombic iron phosphate is larger than that of monoclinic iron phosphate, which is more conducive to the diffusion of lithium atoms during the synthesis of lithium iron phosphate and the formation of orthorhombic lithium iron phosphate. Moreover, the resulting lithium iron phosphate will have better electrical performance, which was also verified in subsequent electrical performance tests.

[0090] Table 1. Crystal form and lattice parameters of each sample

[0091]

[0092] Comparative Example 2

[0093] A method for preparing fully orthorhombic single-crystal iron phosphate is basically the same as that in Example 3, the main difference being the use of high-concentration raw materials. The specific steps are as follows:

[0094] (1) Prepare 100L of 1.6mol / L ferrous sulfate solution, 105L of 1.3mol / L hydrogen peroxide solution and 137L of 1.4mol / L trisodium phosphate solution respectively;

[0095] (2) Add 100L of ferrous sulfate solution to the reactor. The stirring speed of the reactor is 300rpm. Add hydrogen peroxide to the reactor at room temperature for 8 hours. Control the amount of hydrogen peroxide added. Detect the ferrous ions in the reaction solution by potassium permanganate titration. Make sure there is still 3% ferrous sulfate in the reactor.

[0096] (3) Slowly add 137L of trisodium phosphate solution to the reactor over a period of 19 hours, and stir the reactor at 300 rpm.

[0097] (4) Add phosphoric acid to the reaction vessel and adjust the pH of the reaction solution to 1.59. React at 60°C. When the reaction material turns white, add hydrogen peroxide until no ferrous ions can be detected in the reaction solution, that is, the remaining 3% ferrous sulfate is completely oxidized to ferric sulfate (the color does not change when tested with potassium ferricyanide). At this time, 6.54L of 1.3mol / L hydrogen peroxide remains. Then keep warm for 14h. The reaction product is filtered and washed until the conductivity of the wash water is <3000μs / cm. Dry at 120°C for 3h to obtain ferric phosphate.

[0098] The obtained ferric phosphate product was tested by XRD and SEM, and the results are as follows: Figure 10-12 As shown. By Figure 10 It can be seen that the iron phosphate crystals prepared in Comparative Example 2 are, like those in Comparative Example 1, conventional monoclinic crystals. Figure 11-12 As can be seen, the iron phosphate crystals prepared in Comparative Example 2 are the same as those in Comparative Example 1, with primary particles being small flakes of nanometer size (50-100 nm) and secondary aggregates being conventional polycrystalline spheres of micrometer size (5-10 μm).

[0099] Comparative Example 3

[0100] A method for preparing fully orthorhombic single-crystal iron phosphate is basically the same as that in Example 3, the main difference being the change in the way hydrogen peroxide is added, from two additions in Example 3 to one addition. The specific steps are as follows:

[0101] A method for preparing fully orthorhombic single-crystal iron phosphate includes the following steps:

[0102] (1) Prepare 100L of 0.8mol / L ferrous sulfate solution, 105L of 0.8mol / L hydrogen peroxide solution and 137L of 0.7mol / L trisodium phosphate solution respectively;

[0103] (2) Add 100L of ferrous sulfate solution to the reaction vessel. The stirring speed of the reaction vessel is 300rpm. Add hydrogen peroxide to the reaction vessel at room temperature for 8 hours. Control the amount of hydrogen peroxide added. Detect ferrous ions in the reaction solution by potassium permanganate titration. Make sure there are no ferrous ions in the solution in the reaction vessel. All ferrous sulfate is oxidized to ferric sulfate. At this time, 25L of 0.8mol / L hydrogen peroxide is still left.

[0104] (3) Slowly add 137L of trisodium phosphate solution to the reactor over a period of 19 hours, and stir the reactor at 300 rpm.

[0105] (4) Add phosphoric acid to the reactor, adjust the pH of the reaction solution to 1.59, react at 60°C, keep the reaction material white for 14 hours, filter and wash the reaction product until the conductivity of the wash water is <3000μs / cm, and dry at 120°C for 3 hours to obtain iron phosphate.

[0106] The obtained ferric phosphate product was tested by XRD and SEM, and the results are as follows: Figure 13-15 As shown. By Figure 13 It can be seen that the iron phosphate crystals prepared in Comparative Example 3 are, like those in Comparative Example 1, conventional monoclinic crystals. Figure 14-15 As can be seen, the iron phosphate crystals prepared in Comparative Example 3 are the same as those in Comparative Example 1, with primary particles being small flakes of nanometer size (50-100 nm) and secondary aggregates being conventional polycrystalline spheres of micrometer size (5-10 μm).

[0107] Application Example 1

[0108] Lithium iron phosphate was prepared from the iron phosphates obtained in Examples 1-5 and Comparative Examples 1-3 under the same conditions. The specific preparation method is as follows:

[0109] A mixture of ferric phosphate, deionized water, lithium carbonate, and glucose was prepared, wherein the molar ratio of ferric phosphate, deionized water, lithium carbonate, and glucose was 1:2:0.51:0.03. The mixture was then milled to a particle size of 350 nm. The milled slurry was spray-dried, and then sintered at 720 °C for 20 h in a nitrogen atmosphere to obtain lithium iron phosphate.

[0110] Lithium iron phosphate prepared from the iron phosphates of Examples 1-5 and Comparative Examples 1-3 were fabricated into coin cells under the same conditions using conventional methods and named sequentially as 1# coin cell, 2# coin cell, 3# coin cell, 4# coin cell, 5# coin cell, 6# coin cell, 7# coin cell, and 8# coin cell. Their electrical performance was then tested under the same conditions using conventional methods in the art. The electrical performance test results of Examples 1-5 and Comparative Examples 1-3 are shown in Table 2 below.

[0111] As can be seen from Table 2, the initial charge capacity of the coin cells in Examples 1#~5# is 3~5 mAh / g higher than that of the comparative examples 6#~8#, and the discharge efficiency is also 2% higher. This is mainly because the iron phosphate prepared in Examples 1~5# is of the orthorhombic crystal form. From a thermodynamic and kinetic perspective, compared with the monoclinic iron phosphate, it is more conducive to the diffusion of lithium atoms and the formation of lithium iron phosphate during the synthesis of lithium iron phosphate. The compaction density of the coin cells in Examples 1#~3# is also 0.26~0.37 g / cc higher than that of the coin cell in Example 6#. This is mainly because the nucleation and growth rate of single-crystal iron phosphate particles is slower during preparation. Due to the denser growth and the presence of particle size distribution, the prepared lithium iron phosphate has a higher compaction density.

[0112] Table 2 Comparison of electrical performance of various button cells

[0113]

[0114] Table 3 lists a comparison of the rate performance of #3 coin cells (Example 3) and #6 coin cells (Comparative Example 1). From Table 3 and... Figure 16 In comparison, the rate performance of Example 3 is significantly better than that of Comparative Example 1. It still has a capacity of 148.78 mAh / g at 10C and 138.88 mAh / g at 50C, which is significantly better than the capacity of Comparative Example 1 (10C: 110.24 mAh / g, 50C: 75.23 mAh / g).

[0115] Table 3. Rate performance comparison of #3 and #6 coin cells (mAh / g)

[0116]

[0117] Table 4 lists a comparison of the cycling performance of Example 3 (3# coin cell) and Comparative Example 1 (6# coin cell) at a 2C rate. From Table 4 and... Figure 17 As can be seen, the cycle performance of the #3 coin cell is significantly better than that of the #6 coin cell. After 2000 cycles at 2C, the capacity of the #6 coin cell is 126.45 mAh / g, and after 4000 cycles, the capacity is only 100.47 mAh / g. In contrast, the #3 coin cell still has a capacity of 162.66 mAh / g after 2000 cycles at 2C and 161.89 mAh / g after 4000 cycles, with a capacity decay of only 0.000385 mAh / g per week, almost negligible. This is mainly due to its single-crystal structure. Single-crystal particles have a more stable crystal structure and higher mechanical strength, making them less prone to breakage during the lithium insertion / extraction process of charging and discharging, resulting in high stability.

[0118] Table 4 Comparison of Cycling Performance of #3 and #6 Button Cells at 2C Rate (mAh / g)

[0119]

[0120] Although the present invention has been described in detail with reference to the accompanying drawings and preferred embodiments, the present invention is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the present invention. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should also be covered within the protection scope of the present invention.

Claims

1. A method for preparing fully orthorhombic single crystal iron phosphate, characterized in that: The steps include: S1. Adding an oxidant to a reaction vessel containing a ferrous solution, controlling the amount of the oxidant so that after the addition of the oxidant, the mass percentage of the ferrous salt content in the reaction solution to the total solution is 1% to 5%; S2, adding sodium phosphate solution into the reaction vessel while stirring, the stirring speed is 150-550 rpm, the adding time is 15-20 hours, and the concentration of sodium phosphate is 0.4-0.9 mol / L; S3. Add phosphoric acid into the reaction container, adjust the pH value of the reaction solution to 1.57-2.14, react at 50-60°C, add an oxidant after the reaction material turns white until no ferrous ions are detected in the reaction solution, and keep warm for 10-15 hours. Filter, wash and dry the reaction product to obtain fully orthorhombic single crystal iron phosphate.

2. The preparation method according to claim 1, characterized in that The molar ratio of ferrous salt, oxidant and sodium phosphate salt is 1:0.6~0.8:1.1~1.

2.

3. The preparation method according to claim 1, characterized in that: In S1, the concentration of the ferrous solution is 0.4~0.9mol / L.

4. The preparation method according to claim 1, characterized in that: In S1, the iron source of the ferrous solution is selected from at least one of ferrous sulfate, ferrous chloride, ferrous nitrate and ferrous oxalate.

5. The preparation method according to claim 1, characterized in that: In S1, the oxidant is selected from at least one of hydrogen peroxide, air, oxygen, ozone and sodium peroxide.

6. The preparation method according to claim 1, characterized in that: In S1, the oxidant is added while stirring at a stirring speed of 150-550 rpm, and the oxidant is added for 5-10 hours.

7. The preparation method according to claim 1, characterized in that: In S2, the sodium phosphate salt solution is selected from at least one of a trisodium phosphate solution, a disodium phosphate solution and a monosodium phosphate solution.

8. The preparation method according to claim 1, characterized in that: In S3, the reaction product is filtered, washed until the conductivity of the washing water is less than 3000 μs / cm, and then dried at 120° C. for 2 to 5 hours.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery positive pole material lithium iron phosphate and its product

    CN101190785A

  • Battery-grade anhydrous iron phosphate and preparation method thereof

    CN102491302A

Cited By

  • Preparation method of lithium iron phosphate

    CN121849889A